Subtotal hepatectomy in swine for studying small‐for‐size syndrome and portal inflow modulation: is it reliable?. Issue 10 (30th July 2015) - Darnis, Benjamin; Mohkam, Kayvan; Schmitt, Zoé; Ledochowski, Stanislas; Vial, Jean‐Paul; Duperret, Serge; Vogt, Catherine; Demian, Hassan; Golse, Nicolas; Mezoughi, Salim; Ducerf, Christian; Mabrut, Jean‐Yves
Abstract: Background: Small‐for‐size syndrome (SFSS) is a feared complication of extended liver resection and partial liver transplantation. Swine models of extended hepatectomy have been developed for studying SFSS and its different treatment options. Although portal inflow modulation (PIM) by splenectomy or splenic artery ligation (SAL) has been proposed in humans to prevent SFSS, such procedures have not yet been evaluated in swine. Objectives: The present study was designed to evaluate modifications in splanchnic haemodynamics yielded by extended hepatectomy with and without PIM in swine. Methods: Nineteen animals underwent 70% hepatectomy (H70, n  = 7), 90% hepatectomy (H90, n  = 7) or sham laparotomy (H0, n  = 5). Haemodynamic measurements were performed at baseline, after hepatectomy and after PIM by SAL and splenectomy. Results: Portal vein flow increased after both H70 (273 ml/min/100 g versus 123 ml/min/100 g; P  = 0.016) and H90 (543 ml/min/100 g versus 124 ml/min/100 g; P  = 0.031), but the hepatic venous pressure gradient (HVPG) increased only after H90 (10.0 mmHg versus 3.7 mmHg; P  = 0.016). Hepatic artery flow did not significantly decrease after either H70 or H90. In all three groups, neither splenectomy nor SAL induced any changes in splanchnic haemodynamics. Conclusions: Subtotal hepatectomy of 90% in swine is a reliable model for SFSS inducing a significant increase in HVPG. However, in view of the relevant differences between swine and human splanchnic anatomy, this model is inadequate for studying the effects of PIM by SAL and splenectomy.